The legal protection of trademarks in customs legislation, exemplified by the Jordanian Customs Law No. 20 of 1998 and its amendments. - السعيدات عناد عطيه (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This study aimed to explore the role of customs legislation in providing legal protection for trademark owners and preserving intellectual property rights, as well as ensuring consumer safety and health. It addressed the measures for halting customs clearance of goods suspected of infringing trademarks, whether through counterfeiting, imitation, or fraud. The study examined its role in imposing customs control over import and export operations and assessed its effectiveness in preventing the clearance of goods that have been detained, while tracking the fate of goods held at customs centers. The study concluded that the legal rules governing trademark protection in Jordanian Customs Law have not reached an optimal level of protection. They do not result in the confiscation and destruction of counterfeit and forged goods, nor do they ensure the prosecution of those involved in their import and export. This has led to deficiencies and inadequacies in the regulations, rendering them unable to provide complete legal protection. Consequently, there is a need to reconsider the legal texts regulating trademark protection within customs legislation. The study reached several conclusions and recommendations, urging the Jordanian legislator to consider them.